The association of farmers’ cognition, intention and behaviour towards sustainable intensification of cultivated land use in Shandong Province, China - Xiao Lyu; Yuan Liu; Wenlong Peng (International Journal of Agricultural Sustainability)
Cultivated land system confronts with a series of problems hindering its socioeconomic and ecological sustainability. Sustainable intensification of cultivated land use (SICLU) is considered as an efficient method to achieve three aspects of sustainable goals in society, economy and ecology simultaneously. Farmers, the main executor of all agricultural strategies, are the core of SICLU research. However, there is a small quantity of researches on SICLU from the perspective of farmers’ social psychology. Therefore, this article measured the level of SICLU at the farmer scale using super-efficiency SBM model, and relying on structural equation modeling and an innovative research framework, explored the association mechanism among farmers’ cognition, intention and behavior of SICLU. Finally, the results showed that (1) most of samples are at a medium or higher level of SICLU. (2) all samples’ cognition are significantly positively related to their behavior and their behavior significantly negatively affect their intention. (3) correlation characteristics among them are slightly different under each level. The proposed research outline not only expand the scope of SI research to the perspective of social psychology in breadth, but in depth take targeted actions to protect agricultural environment, make cultivated land system sustainable and alleviate food crisis.